Early and late complications after open and endoscopic neurosurgery for complex skull base and craniofacial pathology: Case series, illustrative cases, and review - Paul T. Akins; Levi G. Ledgerwood; Huy T. Duong (Interdisciplinary Neurosurgery, 2022)
Advances in open and endoscopic surgical approaches to the skull base have improved access of patients with formidable skull base and craniofacial pathology to surgical options but carry risks of early and late complications. Methods: We identified complications in a retrospective case series of open and endoscopic complex skull base and craniofacial surgery (N = 60) with comparison to our institutional database for craniotomy (N = 2143). A literature review was completed. Results: Acute complications occurred in 38% of patients, and delayed complications occurred in 17%. Compared to our institutional craniotomy database (n = 2143), complex skull base surgery had higher rates for: any major complication (17% vs 37%); motor deficit (1.7% vs 6.7%); encephalopathy (1.4% vs 6.7%); diabetes insipidus (1.3% vs 8.3%); unplanned OR take back (1.2% vs 38%); symptomatic intracranial bleeding (0.8% vs 15%); CSF leak (0.7% vs 13.3%); deep venous thrombosis (0.4 vs 3.3%); ventilator-associated pneumonia (0.2% vs 3.3%); pulmonary embolus (0.2% vs 1.6%); and pneumocephaly (0.1% vs 3.3%). Thirteen case vignettes highlight: flap-related complications; pseudoaneurysms; CNS vasospasm; sinus thrombosis; osteoradionecrosis-related dural leaks; tension pneumocephalus; low pressure hydrocephalus; airway compromise; hemoptysis; Takotsubo cardiomyopathy; and adrenal crisis. Our literature review identified a wide spectrum of complications (N = 65). Conclusion: Through advances in multimodal treatment with surgery, chemotherapy, and radiation treatment for malignant skull base tumors, survival rates have improved. These survivors remain at risk for both early and delayed complications.